How ethics and status matter in young consumers’ green purchase behavior? Evidence from Vietnam - Dung, Hoang Tuan; Mai, Nguyen Thi Tuyet; Linh, Nguyen Hoang (Edelweiss Applied Science and Technology, 2025)
This study examines some determinants of green purchasing behavior among Vietnamese Generation Z consumers, focusing on the roles of ethics and the need for status through the lens of the Hunt-Vitell theory of ethics. To test the proposed model, a survey was conducted with urban Generation Z consumers, a sustainability-aware cohort that is emerging as a key force in shaping ethical consumption in Vietnam. The results of Partial Least Squares-Structural Equation Modeling (PLS-SEM) indicated that both deontological evaluation and teleological evaluation significantly impacted ethical judgment toward green purchasing. Importantly, ethical judgment, along with the need for status, were found to be significant predictors of green purchase intentions, with ethical judgment exerting a notably stronger influence. As expected, green purchasing behavior was strongly predicted by purchase intentions. These findings underscore the important roles of ethical evaluation and the need for status in understanding consumer pro-environmental purchasing decisions.